Examining the Boundary-Spanning Behaviors of Community-Based Adult EducatorsAn Empirical Examination - Casey D. Mull (Adult Education Research Conference, 2015)
: Community-based adult educators span multiple boundaries, balancing needs of learners, groups, organizations, and institutions. This study contributes not only to the theoretical framework of boundary spanning, but also supports the practice of these adult educators in negotiating a challenging environment.
Keywords: boundary spanning; networked governance; community-based adult educators